2000
DOI: 10.1128/iai.68.4.2156-2160.2000
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Monocyte Urokinase Plasminogen Activator Receptor during Human Endotoxemia

Abstract: The receptor for urokinase-type plasminogen activator (uPAR) (CD87) plays an important role in leukocyte adhesion and migration. To assess the effect of endotoxin on cellular uPAR, uPAR expression was determined on leukocytes by fluorescence-activated cell sorter analysis in seven healthy subjects following intravenous injection of endotoxin (lot G; 4 ng/kg). Endotoxin induced a transient increase in uPAR expression on monocytes, reaching a 92% ؎ 46% increase over baseline expression after 6 h (P < 0.05). Endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
45
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 36 publications
6
45
0
Order By: Relevance
“…In vitro, a number of proinflammatory agents and growth factors such as PMA (23), TGF-␤ and TNF-␣ (24), and nerve growth factor (25) have an enhancing effect on cellular uPAR expression, and uPAR is overexpressed in a number of types of cancerous tumors (26). In the context of infection, LPS in vitro (27,28) and in vivo (29,30), and muramyl dipeptide in vitro (27), can cause an increase in expression of uPAR by monocytes and neoplastic cells. Lyme disease is characterized by inflammatory manifestations in skin, heart, CNS, and joints (2), resulting in tissue damage due to infiltration of inflammatory cells, primarily monocytes/macrophages.…”
mentioning
confidence: 99%
“…In vitro, a number of proinflammatory agents and growth factors such as PMA (23), TGF-␤ and TNF-␣ (24), and nerve growth factor (25) have an enhancing effect on cellular uPAR expression, and uPAR is overexpressed in a number of types of cancerous tumors (26). In the context of infection, LPS in vitro (27,28) and in vivo (29,30), and muramyl dipeptide in vitro (27), can cause an increase in expression of uPAR by monocytes and neoplastic cells. Lyme disease is characterized by inflammatory manifestations in skin, heart, CNS, and joints (2), resulting in tissue damage due to infiltration of inflammatory cells, primarily monocytes/macrophages.…”
mentioning
confidence: 99%
“…Venous blood samples were obtained directly before and 6 h after injection of LPS. (The timing of blood sampling was based on a previous study, in which the effect of intravenous LPS on cellular uPAR expression in humans in vivo was determined [3]). Blood was put on ice immediately, and erythrocytes were lysed with bicarbonate-buffered ammonium chloride solution (pH 7.4).…”
mentioning
confidence: 99%
“…Kingsmore et al studied more than 100 cytokines in septic premature infants, and found that 6 of them, one of which was uPAR, were statistically higher in the sepsis group (25). Pascale et al showed that bacteria and bacterial products influence monocyte function by exerting a stimulating effect on uPAR expression, and tumor necrosis factor alpha (TNF-a) is capable of increasing uPAR mRNA levels in monocytic cells in experimental human endotoxemia (26). Huttunen et al showed that plasma suPAR level is a sensitive and specific independent prognostic biomarker for diagnosing patients with bacteraemia (27).…”
Section: Resultsmentioning
confidence: 99%